Compositing machine design and automation: Agricultural and enviromental implications - Diaz Quinto, Smith Fredy (2025)
Abstract — Automated composting has proven to be a vital solution for the transformation of organic waste into high - quality compost, soil enrichment, and improved agricultural production. This innovation responds to the need to manage urban waste efficiently and mitigate emissions of polluting gases. The implementation of the VDI 2222 Methodology ensures a structured design in key stages, from preparation to compost collection, maximizing its efficiency and quality. The use of black box simulation modeling, backed by probability distributions and precise technology, is an advanced approach to improving the process. The combination of PID controllers and IoT technologies in the control system enables real - time monitoring and adjustment of temperature and humidity, optimizing the process and reducing the environmental footprint. In addition to improving soil quality and food production, this automation is aligned with sustainability goals. Static analysis provides crucial data for the successful design and construction of the composting machine. Efficient composting automation represents an important step towards the convergence of technology and agriculture, addressing current and future challenges in food production and environmental conservation.